FAKTOR LINGKUNGAN LUAR, DAN PERANNYA TERHADAP KEPERCAYAAN BELANJA DI INTERNET DAN PERSEPSI RISIKO PADA KONSUMEN DI SURABAYA - Erika Novita (STIE Perbanas Surabaya, 2011)
Recently, shopping through internet has become a trend throughout the world. This is inter- esting for the researcher to do the research related to it. This study tries to describe a study in which its previously validated measurement instrument is now implemented to investigate the specific factors that are thought to be able to predict the generation of consumers trusts in internet shopping, especially in Surabaya. It actually tests the environmental factor vari- ables that influence the consumers belief in shopping through the internet. It uses the sample that consists of 134 respondents by survey. The questions used are summed to be valid. It shows that third parties recognition has a positive and significant to trust in internet shop- ping. The result that legal framework relates negative significant influence toward the trust in internet shopping. It also shows that the trust on internet shopping has a positive and sig- nificant influence on the perceived risk.